PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PRAKTIK CREATIVE ACCOUNTING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018) - Laras Shatiti; Tarmizi Achmad (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the effect of corporate governance mechanisms proxied by independent commissioners and the quality of external audits, plus two other factors that affecting, there are: profitability and financial leverage on the creative accounting practices (income smoothing) in the manufacturing companies listed on the Indonesia Stock Exchange from 2014-2018. Income smoothing is a management effort to reduce the variation in the number of reported earnings to match the desired target by manipulating earnings through accounting methods or through transactions. This research uses 83 manufacturing companies that were selected as samples by purposive sampling method from total of 170 companies in five years. The samples are classified as smoothers and non-smoothers using income smoothing index (Eckel Index). The hypotheses test is performed using the logistic regression model. The results showed that external audit quality and profitability simultaneously have significant effect on income smoothing. Meanwhile, independent commissioner and financial leverage has no significant effect on income smoothing practice.